Life-Cycle Assessment on Nickel-Metal Hydride Battery in Hybrid Vehicles: Comparison between Regenerated and New Battery: Ocena cyklu życia akumulatora niklowo-wodorkowego w pojazdach hybrydowych: porównanie akumulatora regenerowanego i nowego - Wang, Shuoyao; Yu, Jeongsoo (Investigationes Linguisticae, 2020)
To reduce air pollution and avoid petroleum exhaustion problem, many advanced countries, especially Japan installed Hybrid Vehicles (HV). As the use of HV popularizes around the world, there will be a huge amount of End-of-Life HV in the near future, and the proper treatment of these End-of-Life HVs, especially the waste NiMH (Nickel-Metal Hydride) batteries, will become a serious problem. Currently, the recycling of NiMH battery is gaining substantial attention. However, instead of recycling waste NiMH batteries directly, regenerating and reusing a used NiMH battery for a secondhand HV will largely reduce waste battery generation and demand for new NiMH battery. However, the environmental impact of regenerating and reusing a waste NiMH battery was not clear and has not been compared with the situation when using a brand-new NiMH battery. The purpose of this research is to compare the environmental performance (CO2 emission) of regenerated NiMH battery and brand-new NiMH battery in an HV from their production to usage stage and to discuss the validity of using a regenerated NiMH in Japan and in other countries using the Life-Cycle Assessment (LCA) approach. This research analyzed the composition of a NiMH battery and the CO2 emission during the manufacture, transportation, regeneration and usage process of a NiMH battery. The data used in this research was collected from reports and data published by the government of Japan, vehicle makers and previous studies. Original field survey and interview research on battery regeneration operators were also performed. The result showed that there is not a big difference in environmental effect. Moreover, by doing so, a huge amount of resource will be saved from battery manufacturing process while reducing waste generation. It is recommended that waste NiMH battery should be regenerated and reused in HV instead of being recycled directly in the future.